Proteomics in the fruit tree science arena: New insights into fruit defense, development, and ripening. Issue 12 (10th June 2013) - Molassiotis, Athanassios; Tanou, Georgia; Filippou, Panagiota; Fotopoulos, Vasileios
Abstract : Fruit tree crops are agricultural commodities of high economic importance, while fruits also represent one of the most vital components of the human diet. Therefore, a great effort has been made to understand the molecular mechanisms covering fundamental biological processes in fruit tree physiology and fruit biology. Thanks to the development of cutting‐edge "omics" technologies such as proteomic analysis, scientists now have powerful tools to support traditional fruit tree research. Such proteomic analyses are establishing high‐density 2DE reference maps and peptide mass fingerprint databases that can lead fruit science into a new postgenomic research era. Here, an overview of the application of proteomics in key aspects of fruit tree physiology as well as in fruit biology, including defense responses to abiotic and biotic stress factors, is presented. Α panoramic view of ripening‐related proteins is also discussed, as an example of proteomic application in fruit science.